From Heroic Soldiers to Geometric Forms and Suffering Wrecks: The Transformation of the Male Body in the Art of World War I - Balogh, Eszter Edit (Hungarian Journal of English and American Studies, 2021)
Mechanized and trench warfare, which dominated World War I representations and made millions of soldiers suffer, challenged the rigid gender ideals and hierarchies in the Europe of the time. As the destruction of the traditional manly ideal ran parallel with the destruction of male bodies in the war, the hegemony of traditional representational modes of soldiers was also gradually replaced by more innovative strategies both in poetry and painting. The essay analyzes such works of art with a focus on the crisis of masculinity, manifested quite tangibly in new strategies and representations of visual art. Similarly to soldiers’ written reminiscences, works of visual art depict a sense of emasculation, powerlessness, physical and mental breakdown, testifying that the masculine ideal, which was in large part defined by the chivalric heroic tradition, became anachronistic and unattainable. The figure of the physically or mentally disabled, disempowered soldier as a new phenomenon gained a central position during and after World War I, questioning the validity of the old patriarchal order. Previously marginalized masculinities, for example, the masculinity of homosexual men, and traits previously associated exclusively with femininity such as sensitivity, found their way to open up the borders and shape the Modernist discourse of European masculinity, changing it once and for all. (EEB)